Personnel Management Practices and Academic Staff Job Commitment in Nigerian Colleges of Education - Mafindi, Khadijatu Adanu (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
This study examines the relationship between personnel management practices and academic staff job commitment in Nigerian Colleges of Education, with a focus on the North-East region. Personnel management practices such as recruitment, training and development, motivation, and disciplinary measures were investigated to understand their impact on staff commitment. The findings revealed that merit-based recruitment, continuous professional development, and consistent disciplinary actions positively influence academic staff's commitment. However, challenges such as favoritism in recruitment and external interference in disciplinary actions were identified as impediments to achieving higher levels of job commitment. The study underscores the importance of fair and transparent personnel management practices to enhance staff loyalty, reduce turnover, and improve institutional outcomes. This study employs a correlational research design to examine the relationship between personnel management practices such as recruitment, training, development, motivation, and discipline and academic staff job commitment. It concluded with a recommendation that continuous investment be made on professional development, that disciplinary measures should be apply and stakeholders’ engagement and collaboration.